Desain Pembelajaran Project Insektarium Dalam Mengembangkan Literasi Anak Usia Dini - casini, Casini; Syaodih, Ernawulan (Jurusan PIAUD UIN Siber Syekh Nurjati Cirebon, 2024)
English translation. This study aims to develop a project-based Insectarium learning design to enhance early childhood science literacy at Riyadhul Jannah Kindergarten, Subang. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research process begins with a needs analysis in the field, followed by the design and development stages of learning products in the form of modules and project-based Insectarium learning media. The implementation stage was carried out in the classroom, involving children aged 4-6 years as test subjects. During the learning process, the children were introduced to basic concepts about insects, their habitats, and the important roles insects play in ecosystems through direct observation and documentation activities in the form of an Insectarium.The results of the study indicate that the Insectarium project-based learning design effectively improves children's science literacy, particularly in the aspects of observation skills, basic scientific understanding, and ecological awareness. The learning design product, consisting of a learning module and teaching aids, was validated by early childhood education experts and practitioners, receiving a high feasibility rating. Classroom implementation showed positive responses from children, teachers, and parents, making this learning design suitable for use in enhancing early childhood science literacy. Keywords: SCIENCE literacy; Insectarium; Experiments; PAUD ABSTRAK Penelitian ini bertujuan untuk mengembangkan desain pembelajaran berbasis projek Insektarium dalam upaya meningkatkan literasi sains anak usia dini di Taman Kanak-kanak Riyadhul Jannah, Subang. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Proses penelitian dimulai dengan analisis kebutuhan di lapangan, diikuti dengan tahap desain dan pengembangan produk pembelajaran berupa modul dan media pembelajaran berbasis projek Insektarium. Tahap implementasi dilakukan di kelas dengan melibatkan anak-anak usia 4-6 tahun sebagai subjek uji coba. Selama proses pembelajaran, anak-anak diperkenalkan dengan konsep dasar tentang serangga, habitat, serta peran penting serangga dalam ekosistem melalui kegiatan pengamatan langsung dan dokumentasi dalam bentuk Insektarium. Hasil penelitian menunjukkan bahwa desain pembelajaran projek Insektarium mampu meningkatkan literasi sains anak-anak, terutama dalam aspek keterampilan observasi, pemahaman ilmiah dasar, dan kesadaran ekologis. Produk desain pembelajaran yang dihasilkan berupa modul pembelajaran dan alat bantu pengajaran mendapatkan validasi dari para ahli pendidikan anak usia dini dan praktisi, dengan tingkat kelayakan yang tinggi. Implementasi di kelas menunjukkan respon positif dari anak-anak, guru, dan orang tua, sehingga desain pembelajaran ini layak digunakan untuk meningkatkan literasi sains di kalangan anak usia dini. Kata Kunci: literasi SAINS; Insektarium; Desain Pembelajaran; PAUD